The Effect of the STEM Learning Model on IPA Learning Outcomes of Grade 4 Students at SD Negeri 2 Kotabunan - Rorimpandey, Widdy HF; Modeong, Irshandy (Mimbar Sekolah Dasar, 2024)
The low outcome of IPA (Ilmu Pengetahuan Alam/Science) learning in the Ecosystem topic is a problem in this research so that the use of the STEM learning model is expected to improve IPA learning outcomes. The population in this study was SD Negeri 2 Kotabunan sampled using a cluster random sampling technique and 20 students in Grade 4A and 20 students in Grade 4B were the samples in this study. This research is quasi-experimental using a control group design. The data were collected using test and questionnaires instruments and analyzed using the T test. Test results showed that the significance value was 0.0010.005, or it can be concluded that the STEM learning model affected IPA learning outcomes in the Ecosystem topic. Thus, the STEM learning model can be implemented in learning because it has an effect and can improve the learning outcomes of elementary school students.